MANAJEMEN PONDOK PESANTREN DALAM MENGEMBANGKAN KEWIRAUSAHAAN BERBASIS AGRIBISNIS DI PONDOK PESANTREN TEKNOLOGI PERTANIANAL-ISLAM KAMBITIN - Chairul Echwan (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research is based on the Al- Islam Kambitin Agricultural Technology Islamic boarding school which implements agribusiness- based entrepreneurship education which has a big impact and benefits for the Islamic boarding school and is one of the contributions to completing the kitchen needs and funding of the Islamic boarding school. The aim of this research is to understand the management of Islamic boarding schools in developing agribusiness-based entrepreneurship at the Al- Islam Kambitin Agricultural Technology Islamic Boarding School and its supporting and inhibiting factors. This type of research uses field research and a descriptive qualitative approach. The subjects of this research were Islamic boarding school caregivers, guidance teachers and santri. Data collection techniques use observation, interviews and documentation methods. Meanwhile, the data analysis techniques in this research are data reduction, data presentation and verification. From the research results, it can be seen that Islamic boarding school management in developing agribusiness- based entrepreneurship at the Al- Islam Kambitin Agricultural Technology Islamic Boarding School applies management functions, namely, planning, organizing, mobilizing and supervising. The planning process is carried out through implementing work programs, goals and benefits, up to program targets, carrying out organization by assigning ustaz and santri to assigned tasks according to ability, carrying out mobilization by providing motivation and carrying out supervision and assessment once or twice a month. The supporting factors for agribusiness- based entrepreneurship are weather and human resources, while the inhibiting factors are support from ustad, ustazah, and Islamic boarding school leaders.